The use of low-level laser therapy in nursing practice: an integrative review (Research, Society and Development, 2021)
Objective: To analyze scientific productions about the use of lasers in nursing practice. Methodology: This is an integrative literature review carried out in the Virtual Health Library that includes, among others, the following databases: LILACS, MEDLINE, BDENF, IBECS, CUMED and in the SciELO, PUBMED and Science Direct Online databases, among the years 2016 and 2021. Results: Sixteen studies were analyzed. Regarding the year of publications, it was evidenced that two (02) are from the year 2016 (12.5%); three (03) from 2018 (18.75%); four (04) from 2019 (25%); four (04) of 2020 (25%); three (03) from 2021 (18.75%). Regarding the methodology used in the researches, it was observed that ten (10) are integrative/systematic/bibliographic review (62.5%); two (02) are qualitative (12.5%) and from randomized studies (12.5%); one (01) descriptive study (6.25%) and one (01) methodological study (6.25%). It was identified that the most frequent use in nursing practice is the use of laser as a complementary therapy in the healing process and tissue repair of cutaneomucosal lesions (81.2%), other uses of laser by the nurse observed were: analgesic purpose (25%); complementary therapy in the drainage of edemas and laser acupuncture (18.75%); treatment of fungal infections (12.5%). Conclusion: In the last five years, it was possible to identify the scarcity of scientific production in the area. The production found in national and international databases is incipient and presents methods based on reviews and few clinical studies of high methodological rigor.